Impact of preoperative fasting times on blood glucose concentration, ketone bodies and acid–base balance in children younger than 36 months: A prospective observational study. Issue 12 (December 2015) - Dennhardt, Nils; Beck, Christiane; Huber, Dirk; Nickel, Katja; Sander, Björn; Witt, Lars-Henrik; Boethig, Dietmar; Sümpelmann, Robert
Abstract : BACKGROUND: In contrast to preoperative fasting guidelines in paediatric anaesthesia, actual fasting times are often too long. OBJECTIVE: The objective of this study was to evaluate the effect of preoperative fasting on glucose concentration, ketone bodies and acid–base balance in children. DESIGN: A prospective, noninterventional, clinical observational study. SETTING: A single-centre trial, study period from June 2014 to November 2014. PATIENTS: One hundred children aged 0 to 36 months scheduled for elective paediatric surgery. MAIN OUTCOME MEASURES: Patient demographics, fasting times, haemodynamic data, glucose and ketone body concentrations, and acid–base parameters after induction of anaesthesia were documented using a standardised case report form. RESULTS: Mean fasting period was 7.8 ± 4.5 (3.5 to 20) h, and deviation from guideline (ΔGL) was 3.3 ± 3.2 (-2 to 14) h. Linear regression showed a significant correlation between fasting times and ketone bodies, anion gap, base excess, osmolality as well as bicarbonate (for each, P < 0.05), but not glucose or lactate. In children with ΔGL more than 2 h (54%), ketone bodies, osmolality and anion gap were significantly higher and base excess significantly lower than children with ΔGL less than 2 h (for each, P < 0.05). CONCLUSION: After prolonged preoperative fasting, children younger than 36 months can present with ketoacidosis and (low) normal blood glucose concentrations. Actual fasting times should be optimised according to existing guidelines. In small infants, deviations from fasting guidelines should be as short as possible and not longer than 2 h.